The power of feminist pedagogy in Australia: vagina shorts and the primary prevention of violence against women. Issue 4 (7th June 2017) - Ollis, Debbie
ABSTRACT: This paper examines the challenges of using feminist pedagogies in the development of school-based interventions to address Violence Against Women in Sexuality and Relationships Education in Australia. The focus of the paper is a feminist-based classroom program developed by a group of teachers, which was piloted in three secondary schools in Melbourne. The paper uses interview data from the teachers who taught in the program as well as the students who completed it to explore the feminist discourses embedded in the key program resources. The analysis shows that the program draws heavily on liberal and radical feminist approaches, both perceived by many gender scholars as having limited understandings of gender by comparison with post-modern approaches. The data also indicate that these approaches have the potential to elicit powerful responses from students, raising their awareness of sexism, objectification and sexual safety. The paper concludes by arguing that, while many scholars see post-modern approaches as conceptually superior, they are in practice extremely difficult to operationalize and therefore of limited practical use.